Մասուրի CO2-լուծազատվածքի ազդեցությունը մսային հումքի հասունացման վրա - Դաշտոյան, Ա. Լ.; Պետրոսյան, Ա. Ա. (ՀԱԱՀ հիմնադրամ)
Հում չորացված և հում ապխտած մսամթերքի արտադրության հիմնական ու կարևոր փուլերից են աղադրումը և հասունացումը, որոնց ժամանակ տեղի են ունենում կենսաքիմիական ու մանրէաբանական բարդ պրոցեսներ, առաջանում են ցածրամոլեկուլային միացություններ՝ ապահովելով պատրաստի մթերքի որակը և էներգետիկ արժեքը։ Հետազոտությունների հիման վրա մեր կողմից մշակվել է մասուրի CO2- լուծազատվածքի հավելումով աղադրման նոր եղանակ, որը ոչ միայն կարագացնի մսային հումքի հասունացումը, այլև կնպաստի պատրաստի արտադրանքի օգտակար հատկությունների ավելացմանը։ Одними из основных и важных этапов производства сыровяленых и сырокопченых мясных продуктов являются посол и созревание, в ходе которых протекают сложные биохимические и микробиологические процессы, образуются низкомолекулярные соединения, обеспечивающие качество и энергетическую ценность готового продукта. На основе исследований нами разработан новый способ посола с добавлением СО2-экстракта шиповника, который не только ускорит созревание мясного сырья, но и будет способствовать повышению полезных свойств готового продукта. A salting and ripening process is one of the main and most important steps in producing meat products, especially ground-dried and smoked ones, which undergo complex biochemical and microbiological processes and generate low molecular compounds. This ensures the quality and energy value of a finished product. The development of new methods is therefore necessary to accelerate the ripening process and improve the product›s useful properties. This study aims to develop an optimal dosage of rose hip extract that will accelerate and regulate the ripening process and saturate the high levels of vitamin C in the final product. Maturation was carried out under the same thermal conditions, the duration of maturation was determined by pH. The change in vitamin C content in salted semi-finished meat products was also determined. The research results were compared with the technical regulation of Customs Union Technical Regulations 034/2013 “Safety of meat and meat products”. By introducing this technology in the production of meat products, we will increase the shelf life of the finished product, reducing costs by reducing production costs.
Keywords: Սննդագիտություն և տեխնոլոգիա